IMPLEMENTASI EKSPERIMEN PENGARUH PENGGUNAAN MULSA SERBUK GERGAJI DAN SABUT KELAPA TERHADAP PRODUKSI BAWANG MERAH (Allium Ascalonicum L.) PADA PROSES PEMBELAJARAN HORTIKULTURA - Dewa Nyoman Oka; Herry Maurts Sumampow; Ni Nyoman Serma Adi (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study was conducted to provide students with an understanding of the effect of using sawdust and coconut husk mulch on the production of shallots (Allium ascalonicum L.), and to determine whether this learning model can be applied in the learning process of horticulture courses at IKIP Saraswati. This type of research is experimental, using a simple experimental posttest only control group design. The population of this study were shallot bulbs taken from agricultural shops with relatively the same dryness and weight. The total population is 500 shallot bulbs. From a population of 500 bulbs, 180 bulbs were taken as samples. Sampling was done randomly. This experiment was grouped into 2 groups with three replications. The first group was given coconut coir mulch and the second group was given sawdust mulch. The data obtained in the form of production (wet weight) of shallot bulbs were tested for normality. If the normality requirements have been met, then a parametric analysis with a t-test is carried out. Student learning outcomes using experimental-based learning methods were evaluated using formative assessment. The results of this study indicate that there is a significant difference between the production (wet weight of bulbs) of shallots treated with coconut coir mulch compared to sawdust mulch. Where the treatment with coconut coir mulch gives an average wet weight of shallot bulbs which is superior to sawdust. The use of this experimental-based approach improves students' ability to communicate, and interpret the results obtained from direct observation. It also motivates students to improve cognitive, social, psychomotor and problem solving skills, redefine their theoretical understanding of different concepts, apply deductive and inductive reasoning skills, and encourage collaboration between students. So this experiment needs to be applied in the learning process of horticulture courses at IKIP Saraswati.